“Tau-Omega”- and Two-Stream Emission Models Used for Passive L-Band Retrievals: Application to Close-Range Measurements over a Forest - Mike Schwank (Remote Sensing, 2018)
Microwave Emission Models (EM) are used in retrieval algorithms to estimate geophysical state parameters such as soil Water Content ( <semantics> W C </semantics> ) and vegetation optical depth ( <semantics> τ </semantics> ), from brightness temperatures <semantics> <msubsup> T B p , θ </msubsup> </semantics> measured at nadir angles <semantics> θ </semantics> at Horizontal and Vertical polarizations <semantics> p = { H , V } </semantics> . An EM adequate for implementation in a retrieval algorithm must capture the responses of <semantics> <msubsup> T B p , θ </msubsup> </semantics> to the retrieval parameters, and the EM parameters must be experimentally accessible and representative of the measurement footprint. The objective of this study is to explore the benefits of the multiple-scattering Two-Stream (2S) EM over the “Tau-Omega„ (TO) EM considered as the “reference„ to retrieve <semantics> W C </semantics> and <semantics> τ </semantics> from L-band <semantics> <msubsup> T B p , θ </msubsup> </semantics> . For sparse and low-scattering vegetation <semantics> <msubsup> T B , E M p , θ </msubsup> </semantics> simulated with <semantics> E M = { TO , <mtext> </mtext> 2 S } </semantics> converge. This is not the case for dense and strongly scattering vegetation. Two-Parameter (2P) retrievals <semantics> 2 <mstyle mathvariant="bold" mathsize="normal"> P </mstyle> R C = ( W C R C , τ R C ) </semantics> are computed from elevation scans <semantics> <msubsup> T B p , θ j </msubsup> = <msubsup> T B , TO p , θ j </msubsup> </semantics> synthesized with TO EM and from <semantics> <msubsup> T B p , θ j </msubsup> </semantics> measured from a tower within a deciduous forest. Retrieval Configurations ( <semantics> R C </semantics> ) employ either <semantics> E M = TO </semantics> or <semantics> E M = 2 S </semantics> and assume fixed scattering albedos. <semantics> W C R C </semantics> achieved with the 2S RC is marginally lower ( <semantics> ~ 1 <mtext> </mtext> m 3 m − 3 </semantics> ) than if achieved with the “reference„ TO RC, while <semantics> τ R C </semantics> is reduced considerably when using 2S EM instead of TO EM. Our study outlines a number of advantages of the 2S EM over the TO EM currently implemented in the operational SMOS and SMAP retrieval algorithms.